KEKUATAN HUKUM DAN BATASAN PERJANJIAN BERSAMA TERDAFTAR DALAM KONTEKS UNDANG-UNDANG NOMOR 2 TAHUN 2004 TENTANG PENYELESAIAN PERSELISIHAN HUBUNGAN INDUSTRIAL - Rifa Zulkarnain; Henry Aspan (International Journal of Synergy in Law, Criminal, and Justice, 2025)
Industrial relations disputes are a common phenomenon in employment relations between employers and workers. The resolution of these disputes is very important to maintain the stability of conducive and fair industrial relations for both parties. In the legal system in Indonesia, the resolution of industrial relations disputes is regulated in Law Number 2 of 2004 concerning the Settlement of Industrial Relations Disputes. One form of settlement accommodated by this law is through a Joint Agreement (PB). This study aims to determine the legal basis of the Joint Agreement in resolving industrial relations disputes, and how the execution of the registered Joint Agreement is determined and the legal efforts that can be taken against the execution of the registered Joint Agreement. The research method used in this study is the normative legal research method, by looking at, studying, and understanding legal materials, based on positive legal studies. From this study it can be concluded that the legal basis of the Joint Agreement is regulated in Articles 3 and 7 of Law Number 2 of 2004 concerning the Settlement of Industrial Relations Disputes, where the Joint Agreement is the result of the settlement of industrial relations disputes in a bipartite manner. The determination of the execution of the registered Joint Agreement is carried out through an application for execution at the Industrial Relations Court at the District Court in the area where the Joint Agreement is registered to obtain an execution determination. The legal remedies for the determination of the execution of the registered joint agreement are through the legal remedies of Cassation and Derden Verzet. This is because based on the provisions of Article 57 of Law Number 2 of 2004 concerning the Settlement of Industrial Relations Disputes which explains that the procedural law applicable to the Industrial Relations Court is the Civil Procedural Law applicable to the Courts within the General Court environment.